2012
DOI: 10.1007/s00330-012-2411-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous MR-guided cryoablation of prostate cancer: initial experience

Abstract: • Magnetic resonance allows precise positioning of cryoprobes with real-time imaging. • High-resolution MRI allows excellent monitoring of the developing ice ball. • Cryoablation of prostate cancer under MR guidance is technically feasible. • Further work will refine the procedure and make it even safer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 30 publications
1
52
0
1
Order By: Relevance
“…Gangi et al reported on 11 patients who underwent MRI-guided cryoablation of the entire prostate. With technical success in 10/11 patients, only one major complication with a spontaneously healing rectourethral fistula occurred [71]. Bomers et al reported similar data regarding focal MRI-guided cryoablation in the case of relapse after radiation therapy of prostate cancer.…”
Section: Prostatementioning
confidence: 77%
“…Gangi et al reported on 11 patients who underwent MRI-guided cryoablation of the entire prostate. With technical success in 10/11 patients, only one major complication with a spontaneously healing rectourethral fistula occurred [71]. Bomers et al reported similar data regarding focal MRI-guided cryoablation in the case of relapse after radiation therapy of prostate cancer.…”
Section: Prostatementioning
confidence: 77%
“…This is currently, possible performing cryosurgery under MRI guidance instead of transrectal ultrasound guidance. To date, only limited data about MRI-guided cryosurgery study of the prostate are available [14]. During the Laser Ablation Treatment, a laser fiber is positioned in the tumor under imaging guidance (ultrasound or MRI) destroying the tissue by the raising of the temperature than 60°C.…”
Section: Discussionmentioning
confidence: 99%
“…-20°C buz küresinin içerisin-dedir. Bu, buz küresinden daha küçük bir alanın nekroza gittiğini göstermiştir [52,53].…”
Section: Eği̇ti̇ci̇ Noktaunclassified